Influence of antithymocyte globulin treatment of brain‐dead organ donor on inflammatory response in cardiac grafts: an experimental study in mice. (30th September 2016) - Kremer, Jamila; Muschitz, Gabriela K.; Aumayr, Klaus; Moser, Philipp; Szabo, Gabor; Weymann, Alexander; Zuckermann, Andreas; Podesser, Bruno K.
Summary: The expression of proinflammatory cytokines in donor hearts after antithymocyte globulin (ATG) treatment given prior to organ removal was evaluated to analyze changes in inflammatory response. Adult female OF‐1 mice were randomized into brain death (BD) groups (BD Control, BD ATG) with or without treatment, and Controls (Control, ATG). BD induction was performed through gradual inflation of an intracranial positioned balloon catheter. At the end of a 6‐h observation period, ATG (1 mg/kg BW) was given intravenously. After 45 min, the donor hearts were removed. Proinflammatory markers IL‐2 and IL‐6 were examined using ELISA and immunohistochemistry staining. After single administration of ATG, the inflammatory reaction in the myocardium showed a significant reduction in IL‐2 expression (BD Control vs. BD ATG, P = 0.033). Our investigation showed expected increase in proinflammatory mediators after BD. This increase was abolished by single infusion of ATG, indicated by significant reduction in IL‐2 levels in the myocardium. We observed a reduction of IL‐6 deposition in media cells in ATG‐treated specimens. Further research is necessary to evaluate the role of ATG in donor management considering a potentially positive effect of ATG on IL‐2‐directed inflammatory response and possible reduction of IL‐6‐mediated vascular changes.